TITANIUM NANOPARTICLES CONJUGATED WITH STREPTOKINASE AS A MODIFIED THROMBOLYTIC AGENT - ABED, HAYDER H.; ALWASITI, ESTABRAQ AR.; TAWFEEQ, AMIR T. (International Journal of Current Pharmaceutical Research, 2020)
Objective: Blood clots are the main cause of death worldwide by stroke and myocardial infarction. Streptokinase a thrombolytic agent that is used in the treatment of circulatory disorders. Methods: Titanium Nanoparticles was supplied from Changsha Santech Co. Its characterized were studied using (FT-IR, XRD, AFM, FE-SEM). Streptokinase at concentration 0.1 mg/ml was conjugated with Titanium nanoparticles using PH equal to 5.2 with continuous stirring. Formation of Streptokinase loading Titanium nanoparticles confirmed using FT-IR, Ninhydrine’s test and Bradford protein assay. Physicochemical Properties were studied in vitro. Thrombolytic activity in vitro was determined using d–dimer indicator and weight of blood clot after treatment as indicators of thrombolytic activity. Results: Titanium nanoparticles show particle size at range 31 nm. The thrombolytic activity of streptokinase loading Titanium nanoparticles shows significant value in d-dimer and weight of blood clot compared with the control group and non-significant compared with an equivalent amount of streptokinase alone. Conclusion: Titanium nanoparticles conjugated with streptokinase show high thrombolytic activity against blood clots in vitro.